Bidirectional Ventricular Tachycardia with Stress-Induced Cardiomyopathy. (27th April 2022) - Schreiber, Ariyon; Gardner, Michael; Sossou, Chris; Greene, Natasha; Ahsan, Chowdhury
Abstract : Bidirectional ventricular tachycardia (BDVT) is a rare electrocardiographic finding characterized by rapid, wide complex, alternating QRS morphology with 180-degree swings in the frontal plane axis or, less commonly, alternating right bundle branch and left bundle branch block morphology. The most proposed mechanisms for BDVT involve triggered activity or enhanced automaticity resulting from calcium dysregulation. Catecholamine surge can cause myocardial injury as well as calcium dysregulation resulting in enhanced automaticity that can lead to arrhythmias such as BDVT. This case report stands to describe a unique presentation of BDVT and stress-induced cardiomyopathy, resulting from catecholamine surge following multiple traumatic gunshot wounds in the setting of methamphetamine use.